PECULIARITIES OF ADOLESCENTS' LIFE PLANS IN DIFFERENT TYPES OF VALUE ORIENTATION - A. V. Poletaeva (Вестник Кемеровского государственного университета, 2013)
Тhe article considers the structure and content of adolescents' life plans, the most valuable and significant spheres of life, the meaning of life and their satisfaction with it in such types of value orientation as: schizoid, neurotic, narcissistic.